The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2298/tsci2106003w
|View full text |Cite
|
Sign up to set email alerts
|

Energy saving technology of wall insulation of harbor building based on energy cost analysis

Abstract: Seaport buildings have been affected by marine moisture for a long time, but most of the wall thermal insulation studies have not considered the moisture transfer effect of the wall structure. Therefore, considering the moisture transfer function of the wall structure and the energy consumption of solar radiation, based on the energy cost analysis, the paper puts forward the research on the wall thermal insulation and energy-saving technology of the harbor building based on the energy cost an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…As the mining depth increases, the difficulty of mining also increases. Deep coal resources will encounter problems such as high ground stress, high ground temperature and high osmotic pressure, which will cause hidden dangers to safety production [3][4][5]. Among them, the effect of high ground temperature mainly causes mine heat damage, which is divided into two categories: high temperature heat damage and high humidity heat damage.…”
Section: Introductionmentioning
confidence: 99%
“…As the mining depth increases, the difficulty of mining also increases. Deep coal resources will encounter problems such as high ground stress, high ground temperature and high osmotic pressure, which will cause hidden dangers to safety production [3][4][5]. Among them, the effect of high ground temperature mainly causes mine heat damage, which is divided into two categories: high temperature heat damage and high humidity heat damage.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of building energy efficiency, thermal insulation materials have gradually become the focus of attention in order to realize the strategic goal of sustainable development in China [9,10]. Wang et al [11] used two insulation materials and three insulation positions to analyze the thermal performance of a wall. It was found that increasing the thickness of the insulation layer was a favorable method to reduce heat loss from the wall.…”
Section: Introductionmentioning
confidence: 99%
“…The development of urban construction promotes rapid expansion of advanced building and materials industry [1]. The structural and thermal properties of multilayer building components play a key role not only in hygrothermal and acoustic comfort but also in energy performance of building's envelope [2].…”
Section: Introductionmentioning
confidence: 99%